Methodology Of Applying The Acmeological Approach In Higher Education (Journal of Pedagogical Inventions and Practices, 2025)
This article analyzes the methodology of applying the acmeological approach in higher education. As a science that studies the laws of achieving the highest levels of personal and professional development, acmeology contributes to enhancing students’ creative potential, independent thinking, and motivation for self-improvement. The paper discusses the ways to improve the educational process based on the acmeological approach, the teacher’s leading role, and the mechanisms of self-awareness and selfrealization. The research results provide a methodological basis for the effective implementation of the acmeological approach in higher education institutions.